Millimeter wave p–i–n-diode switching controlled devices - Karushkin, N. F.; Malyshko, V. V.; Orekhovsky, V. V.; Tuharinov, A. A. (Technology and design in electronic equipment, 2016)
The paper presents the results of research and development of concentrated type p–i–n-diodes switches providing the switching time units of nanoseconds. To increase lock losses of ( 40 dB) the authors use a cascade connection of diodes into waveguide and microstrip transmission line of θ = π/2 electric length. Investigation results of creation of switching devices using longitudinally and transversely-distributed p–i–n-structures in the shortwave part of the millimeter wavelength range (f = 300 GHz) are presented. When developing switching devices intended to control the level of microwave power in the millimeter wavelength range, a number of special features arise limiting the achievement of optimal parameters. The dimensions of the metal ceramic packaged p–i–n-diodes and the mounting elements of semiconductor structures become comparable with the wavelength. As a result, package cannot be considered in the calculations and in the design as the capacity of the concentrated type. In our case the diode package is considered in the form of radial line which is able to transform the input impedance of the transmission line to the terminals of the diode structures, and realize high-impedance state (parallel resonance) in the device circuit in the mode of microwave power transmission. Engineering calculations for the given parameters of the silicon mesostructures showed the possibility of creating high-speed devices for switching microwave power with good characteristics. For diode assembling industrial clockwork ruby jewels with high quality of surface finish, strength and appropriate dimensions are applied as dielectric bushings. Suffice it to say that in the frequency range of 150 GHz, we used the bushings with dimensions of external diameter D = 0.4 mm and a height of h = 0.15 mm. The switches created provide transient units of nanoseconds, isolation more than 40 dB at relative frequency bandwidth of 30-40%. Evaluating progress in the development of millimeter wavelength devices, it should be noted that at frequencies greater than 200 GHz, the application of the concentrated type diodes is problematic. In this range, it would seem to be promising to use bulk semiconductors. In this case, surface-oriented p–i–n-structures can be applied as unified elements of the control devices in the shortwave part of the millimeter range, as well as in quasi-optical transmission lines.